2015
DOI: 10.1186/s12891-015-0784-y
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet induced ischemia and changes in metabolism during TKA: a randomized study using microdialysis

Abstract: BackgroundTourniquet use in total knee arthroplasty (TKA) surgery is applied to minimize blood loss thereby creating better overview of the surgical field. This induces ischemia in the skeletal muscle resulting in reperfusion injury. Our aim was to investigate the in vivo metabolic changes in the skeletal muscle during TKA surgery using microdialysis (MD).MethodsSeventy patients were randomly allocated to tourniquet group (n = 35) or non-tourniquet group (n = 35). Prior to surgery, catheters were inserted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 15 publications
1
29
1
Order By: Relevance
“…The cell changes its metabolism from oxidative phosphorylation to anaerobic glycolysis to generate energy and preserve homeostasis. Accordingly, a reduction of oxygen supply will decrease the production of pyruvate with a following increase in lactate, resulting in an increase in the lactate/pyruvate (L/P) ratio (14,19). A L/P ratio above 25 is considered to signify ischemia (20).…”
Section: Study Proceduresmentioning
confidence: 99%
“…The cell changes its metabolism from oxidative phosphorylation to anaerobic glycolysis to generate energy and preserve homeostasis. Accordingly, a reduction of oxygen supply will decrease the production of pyruvate with a following increase in lactate, resulting in an increase in the lactate/pyruvate (L/P) ratio (14,19). A L/P ratio above 25 is considered to signify ischemia (20).…”
Section: Study Proceduresmentioning
confidence: 99%
“…In animal studies, it has been shown that serum creatinine phosphokinase (CPK), a marker of muscle damage, does not begin to rise until approximately 2 hours. 42 Ejaz et al 43 conducted a prospective RCT that utilized microdialysis to measure metabolic changes within skeletal muscle during TKA. They found that the levels of ischemic byproducts such as lactate and glycerol rose by 116 and 190%, respectively, whereas energy sources such as glucose and pyruvate decreased by 54 and 60%, respectively.…”
Section: Metabolic Disturbance and Wound Healingmentioning
confidence: 99%
“…The cellular bioenergetics and mitochondria are preserved during skeletal muscle I/R in the TKA setting [ 11 , 18 , 19 ]. For example, (1) adenosine triphosphate (ATP) concentrations and mitochondrial enzymes were maintained during 60–90 minutes of ischemic time and at 24 hours after reperfusion [ 11 , 18 ], despite significant metabolic changes which suggested ischemic injury to the skeletal muscle cell at approximately 75 minutes of ischemia [ 20 ], and (2) a previous human study [ 19 ] showed mitochondria to have normal appearance when viewed under an electron microscope after 15 minutes of ischemia. However, in cases of myocardial I/R condition, mitochondrial respiratory chain activity was reduced after 30 minutes of ischemia and restored upon reperfusion as a biphasic process [ 21 , 22 ].…”
Section: Effects Of Tq-induced I/r Injury On Localized Skeletal Mumentioning
confidence: 99%